Unmet needs in patients with moderate-to-severe plaque psoriasis treated with methotrexate in real world practice: FirST study. (3rd April 2022) - Rivera, Raquel; Vilarrasa, E.; Ribera, M.; Roe, E.; Kueder-Pajares, T.; Zayas, A. I.; Martínez-Molina, L.; Mataix Díaz, J.; Rodríguez-Nevado, I. M.; Usero-Bárcena, T.; de la Mano, D.; García-Donoso, C.; et al.
Abstract: Background: Methotrexate (MTX) is frequently used in the treatment of moderate-to-severe psoriasis, however, there is limited data on health-related quality-of-life (HRQoL), psoriasis clinical outcomes and hepatic fibrosis in MTX-treated patients in routine clinical practice. Objectives: To investigate the impact of moderate-to-severe psoriasis in MTX-treated patients in Spain regarding to HRQoL, psoriasis clinical data and risk of hepatic fibrosis. Methods: Observational, non-interventional, cross-sectional, retrospective, multicentre study, performed in Spain in moderate-to-severe plaque psoriasis patients treated with MTX > 16 weeks prior to inclusion. Results: Despite ongoing treatment, 17.1% of 457 evaluable patients reported moderate-to-extreme impact on HRQoL (DLQI > 5); 21.4% BSA > 5 and 35.2% moderate-to-severe pruritus (VAS ≥ 4). Persistent severe psoriasis (PASI ≥ 10 and/or DLQI ≥ 10) was observed in 10.7%. Hepatic steatosis was identified in 64.1% of patients (HSI ≥ 36) and 37.2% of the patients were at-risk of advanced fibrosis which was associated to the MTX treatment duration. Conclusions: The study identified unmet needs in moderate-to-severe plaque psoriasis patients treated with MTX, revealing a significant proportion of sub-optimally controlled patients in terms of HRQoL and different domains of the disease. This study also found patients at-risk of advanced fibrosis, with evidence suggesting a correlation between longer exposures to MTX and higher risk of advanced fibrosis.